2020
DOI: 10.1007/s12975-020-00784-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Successful First-Pass Thrombectomy with a Balloon Guide Catheter: Results of a Decision Tree Analysis

Abstract: Complete recanalization after a single retrieval maneuver is an interventional goal in acute ischemic stroke and an independent factor for good clinical outcome. Anatomical biomarkers for predicting clot removal difficulties have not been comprehensively analyzed and await unused. We retrospectively evaluated 200 consecutive patients who suffered acute stroke and occlusion of the anterior circulation and were treated with mechanical thrombectomy through a balloon guide catheter (BGC). The primary objective was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Thus, identifying factors influencing FPE could help clinicians and interventionalists maximize the benefit of MT through suitable patient selection and pre-interventional risk modification. There are many studies seeking to explore this phenomenon, but with inconsistent results (7,8,11,(13)(14)(15)(16)(17)(18)(19)(20). For example, balloon guide catheters (BGC) and non-internal carotid artery (ICA) terminus occlusion were correlated with FPE in the study of Zaidat et al (7), but factors such as older age, a lower systolic blood pressure, and conscious sedation were not (17).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, identifying factors influencing FPE could help clinicians and interventionalists maximize the benefit of MT through suitable patient selection and pre-interventional risk modification. There are many studies seeking to explore this phenomenon, but with inconsistent results (7,8,11,(13)(14)(15)(16)(17)(18)(19)(20). For example, balloon guide catheters (BGC) and non-internal carotid artery (ICA) terminus occlusion were correlated with FPE in the study of Zaidat et al (7), but factors such as older age, a lower systolic blood pressure, and conscious sedation were not (17).…”
Section: Introductionmentioning
confidence: 99%
“…But, this finding was not an independent factor for FPE in their research. Contrary to this, Gonzalez et al 34 found that the success rate of FPE was lower in women in patients with anterior circulation stroke. These inconstant findings may be due to ethnical and genetic features, or unknown multifactorial variables, which require further investigation in the future.…”
Section: Discussionmentioning
confidence: 85%
“…Some authors reported similar results with us 5,10 while some studies found that FPE was lower in female patients. 7 Differences in ethnic features in these study cohorts or unidentified multiple variables may be the reasons for this inconsistency. A higher baseline ASPECT score was also noticed as a predictor of FPE in a large prospective study, similarly to us.…”
Section: Discussionmentioning
confidence: 95%
“…5,6 Since it is understood in these articles that the primary ambition in MT is to achieve FPE; clinical, demographic, laboratory, procedural, and anatomical factors associated with FPE have turned into an intriguing topic nowadays. [7][8][9][10] Nevertheless, predicting FPE by only evaluating the pretreatment imaging modalities is still impossible.…”
Section: Introductionmentioning
confidence: 99%